2019
DOI: 10.1002/jcb.29352
|View full text |Cite
|
Sign up to set email alerts
|

Silencing vascular endothelial growth factor C increases the radiosensitivity in nasopharyngeal carcinoma CNE‐2 cells

Abstract: Vascular endothelial growth factor C (VEGF‐C) has been reported to be responsible for the lymphatic vessel density, tumor staging and lymph node metastasis, resulting in the failure of nasopharyngeal carcinoma (NPC) after radiotherapy. Therefore, the aim of this study was to explore the effects and the underlying mechanism of VEGF‐C on the radiotherapy and in the human NPC cell lines CNE‐2. In our study, VEGF‐C silenced CNE‐2 cells were stably established. Different small interfering VEGF‐C (si‐VEGFC) were tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…VEGF has been proved to be involved in the occurrence and development of tumors, and is closely related to the prognosis of patients (Siemann, Chaplin, and Horsman 2017). In recent years, many studies have found that inhibiting VEGF expression can improve the sensitivity of many types of cancer to radiotherapy (Chen et Wang et al 2020). In this study, we also found that siRNA knocks down VEGF expression in ESCC cell line to signi cantly inhibit the growth and proliferation of cells after radiotherapy, which is similar to Chen's research results (Chen et al 2015).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…VEGF has been proved to be involved in the occurrence and development of tumors, and is closely related to the prognosis of patients (Siemann, Chaplin, and Horsman 2017). In recent years, many studies have found that inhibiting VEGF expression can improve the sensitivity of many types of cancer to radiotherapy (Chen et Wang et al 2020). In this study, we also found that siRNA knocks down VEGF expression in ESCC cell line to signi cantly inhibit the growth and proliferation of cells after radiotherapy, which is similar to Chen's research results (Chen et al 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, VEGF is found to have relaitionship with radioresistance in solid tumors recent years (Buckley et al 2020). In the study of Wang et al (Wang et al 2020), VEGF-C stable and silent nasopharyngeal carcinoma cells were established, and it was found that combined radiotherapy signi cantly inhibited the proliferation and growth ability, and induced nasopharyngeal carcinoma. It makes cell apoptosis and DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…IL11RA encodes the IL-11 receptor, and mutations in this gene cause autosomal recessive Crouzon‐like craniosynostosis [ 54 ] and affect thymus immune function [ 55 ]. Vascular endothelial growth factor C ( VEGFC ) is a determinant of lymphatic vessel density, tumor staging, and lymph node metastasis, and is associated with the failure of nasopharyngeal carcinoma to respond to radiotherapy [ 56 ]. Autophagy related 10 ( ATG10 ) is a critical gene for autophagy and cancer, and there is increasing evidence for the importance of autophagy-related genes in the maintenance, therapy, and pathogenesis of cancer [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…High expression of VEGFC is significantly associated with poor prognosis in various malignancies, including lung cancer [ 44 ], gastric cancer [ 45 ], thyroid cancer [ 46 ], colorectal cancer [ 47 ], and HNSCC [ 48 ]. Furthermore, a study showed that silencing VEGFC can increase the radiosensitivity of nasopharyngeal carcinoma CNE-2 cells [ 49 ].…”
Section: Discussionmentioning
confidence: 99%